Behaviour of Steel-Soil Bridge Structure Made of Corrugated Plates Under Field Load Tests. Part II: Dynamic research - Mańko, Zbigniew; Bęben, Dariusz (Engineering Transactions, 2006)
The paper presents the results and conclusions of dynamic load tests that were conducted on a road bridge over river Girmån in Sweden (the first bridge of this type in Scandinavia) made from Super Cor corrugated steel plates. Conclusions drawn from the tests can be mostly helpful in the assessment of behaviour of this type of corrugated plate bridge with backfill. In consideration of application of this type of structure in the case of small-to-medium more and more frequent span of bridges, the conclusions from the research will be generalized to all types of such solutions.